Water temperature, salinity and oxygen data in front of GEOMAR Pier, Kiel, Germany (2020-2021) - Claas Hiebenthal; Björn Buchholz; Frank Melzner (PANGAEA, 2023)
From January 2020 to October 2021, seawater temperature and salinity data were measured repeatedly by a hand-held salinity probe (WTW Handheld ProfiLine Multi 3320 with conductivity measuring cell TetraCon 325) at GEOMAR (Kiel, Germany) pier at 54°19 extquotesingle48.8N 10°08 extquotesingle59.6E. The seawater was continuously pumped from 1m depth to a container on the extquotesingleKiel Outdoor Benthocosm extquotesingle (KOB) platform in which the measurement took place. The sensor was calibrated prior to each measurement.